Simulation of wireless communications system among labwiev - Shpin, Aleksandr; Krivtsov, Vycheslav (Видавництво Львівської політехніки, 2012)
Using the software package LabVIEW tools developed computer models of wireless communication channel with the possibility of their use in practical studies.
Keywords: Virtual tools; Environment LabVIEW; coefficient of BER; Spectrum analysis; Noise stability